Determination of Peak Aerobic Capacity in Normal Weight Obesity and Metabolically Healthy Obesity. (7th June 2021) - Hart, Samantha; Keirns, Bryant; Sciarrillo, Christina; Guynes, Reese; Emerson, Sam
Abstract: Objectives: The true cardiometabolic risk of the novel body composition phenotypes normal-weight obesity (NWO) and metabolically healthy obesity (MHO) remains controversial. Cardiorespiratory fitness, as measured by peak oxygen uptake during exercise (VO2peak ), is inversely correlated with CVD and mortality. The objective of this project was to determine VO2peak in NWO and MHO relative to appropriate positive and negative control groups. Methods: For this cross-sectional study, participants aged 18–50 years were recruited into one of four groups based on BMI, body composition, and metabolic risk factors: NWO (normal BMI with high body fat percentage (BF%)); MHO (obese BMI, high BF%, and up to one of the diagnostic criteria for metabolic syndrome (MetS) as defined by the International Diabetes Federation); MetS (obese BMI, high BF%, and at least three of the diagnostic criteria for MetS); and healthy controls (HC; normal BMI, BF%, and metabolic markers). Participants engaged in a maximal exercise test on a cycle ergometer to determine VO2peak and a DEXA scan to assess BF%. Data were analyzed using one-way ANOVA. Results: A total of 35 participants completed this study (HC: n  = 10; NWO: n  = 8; MHO: n  = 10; MetS: n  = 7). VO2peak was greater in HC (44.2 ± 11.0 ml/kg/min) compared to NWO (28.6 ± 5.1 ml/kg/min; P  = 0.002), MHO (25.4 ± 6.7 ml/kg/min; P < 0.0001) and MetS (24.3 ± 8.8 ml/kg/min; P  = 0.0002). VO2peak was similar among NWO, MHO, and MetS (p's ≥ 0.76). BF% was lower in HC (23.4 ± 5.5%) compared to NWO (32.6 ± 3.8%; P  = 0.0099), MHO (41.9 ± 6.0%; P < 0.0001) and MetS (32.5 ± 6.1%; P  = 0.016). BF% was also greater in MHO compared to NWO ( P  = 0.0085) and MetS ( P  = 0.0115). There was no significant difference in BF% between NWO and MetS ( P > 0.9999). Across groups, there was a strong inverse correlation between BF% and VO2peak (r = −0.83). Conclusions: VO2peak did not significantly differ among all three at-risk groups (NWO, MHO, and MetS), and all were lower than HC. BF% also did not significantly differ between NWO and MetS groups, and BF% was actually greater in MHO compared to MetS and NWO. NWO and MHO, despite normal BMI and metabolic markers, respectively, have a VO2peak more similar to MetS than HC, suggesting increased cardiometabolic risk. Funding Sources: American Society for Nutrition Mars. Inc Predoctoral Fellowship.